1979
DOI: 10.1111/j.1365-2222.1979.tb01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Group comparative trial of 2% sodium cromoglycate (Opticrom) with placebo in the treatment of seasonal allergic conjunctivitis

Abstract: Summary A double‐blind group comparative trial comparing Opticrom with a matching placebo, over a four‐week period, in seasonal allergic conjunctivitis is reported. Overall assessment of treatment benefit made at the end of the trial by the patients and the clinician showed a statistically significant difference in favour of Opticrom. Of the patients on Opticrom, eighteen (90%) said they improved while in the clinicians opinion, seventeen (85%) improved. Six patients using Opticrom and five using placebo compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Sodium cromoglycate has been shown to be effective in various allergic disorders of the eye including SAC [7][8][9]. Sodium cromoglycate is a synthetic chromone compound of low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium cromoglycate has been shown to be effective in various allergic disorders of the eye including SAC [7][8][9]. Sodium cromoglycate is a synthetic chromone compound of low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…They do this by acting as a barrier to prevent allergen from attacking the conjunctival surface, helping to dilute allergen and mediators in the tear film, and acting as an eyewash. Such environmental studies are known to have placebo effect ratings as high as 50% and 60% [23,24]. Although it is difficult to completely eliminate, the placebo effect is a significant factor, and it can be expected to play a larger role in environmental studies in which it acts as an eyewash, compared with single-drop studies in the CAC model.…”
Section: Factors Affecting Data In the Environmental Modelmentioning
confidence: 97%
“…Although two studies showed equivalent efficacy of cromones and terfenadine, the efficacy of cromones in SAR has been questioned, especially when compared to topical corticosteroids and antihistamines ( 105, 123, 124). Comparisons between topical corticosteroids and DSCG or topical antihistamines and DSCG in patients with seasonal AR demonstrated the greater efficacy of both drugs over DSCG, for both symptom control and patient compliance (due to the multiple daily administration necessary for DSCG) ( 105, 122).…”
Section: Cromonesmentioning
confidence: 99%